The Effect of Financial Self-Efficacy on Student Investment Interest Mediated by Financial Literacy - Yamani, Az Zahra Nabilah; Munir, Misbahul (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Along with the development of the capital market in Indonesia also continues to grow. An increase in the number of investors in the capital market marks this. Generation Z and millennials dominate the growth of investors in the capital market. However, the education history of investors with the last bachelor's degree is less than those with an equivalent high school education history. This study aims to determine what factors will increase student investment interest in the capital market. This study uses quantitative methods with an associate's approach. This study hypothesizes that there is an influence between financial self-efficacy on investment interest and financial literacy, there is an influence of financial literacy on investment interest. Financial literacy can mediate financial self-efficacy with investment interest.